Influence of Leading Entrepreneurship Training Program Bank Indonesia in the Business of Increasing MSME Income in the City of Pematangiantar - Abdi Setiawan; Pinondang Nainggolan; Bagudek Tumanggor; Darwin Damanik (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to explain the effect of Bank Indonesia's flagship entrepreneurship training program in increasing the income of MSMEs in the city of Pematagsiantar. The research design is quantitative research. Data collection techniques using a list of questions (questionnaires) and study documentation. The data analysis technique uses the Assumption Test contained in the regression analysis used, namely normality test, autocorrelation test, heteroscedasticity test, and multicollinearity test, Hypothesis Testing namely Simultaneous Test (F test), Partial Test (t test), Coefficient of Determination (R2),Correlation Coefficient (R)andRegression Analysis.Based on the research, it was found that Bank Indonesia's flagship entrepreneurship training program, production facilities and labor played a good role in increasing the income of MSMEs in Pematangsiantar City. Based on the t test, it was found that the X1 variable had no significant effect on the Y variable, the X2 variable had no significant effect on the Y variable, the X3 variable had a significant effect on the Y variable.